Acoustic backscatter observations with implications for seasonal and vertical migrations of zooplankton and nekton in the Amundsen shelf (Antarctica). (5th January 2015) - La, H.S.; Ha, H.K.; Kang, C.Y.; Wåhlin, A.K.; Shin, H.C.
Abstract: High-temporal resolution profiles of acoustic backscatter were collected in the Dotson Trough on the Amundsen shelf in the Antarctica, using a bottom-moored, upward-looking acoustic Doppler current profiler (ADCP). This data set was used to examine the impact of seasonal variations in surface solar radiation (SSR), sea ice concentration (SIC), and Circumpolar Deep Water (CDW) thickness on acoustic backscatter in the lower water column (250−540-m depth). A recorded high acoustic backscatter (−75 to −70 dB) at depth >400 m from April to November compared to the rest of the year (−90 to −80 dB) suggests that zooplankton and nekton migrated towards the bottom during winter. The depth of maximum mean volume backscattering strength showed a significant correlation with SSR, SIC and CDW thickness. A daily cycle of vertical migration was also recorded. This varied with changing surface ice conditions. When sea ice cover was low, the acoustic backscatter descended at sunrise, and ascended at sunset. When sea ice cover was high, the daily migration was not pronounced, and the layer of high acoustic backscatter remained near the bottom. This is the first study of seasonal and vertical migration of zooplankton and nekton that has been conducted on the Amundsen Sea shelf, one of the world's most productive areas. The findings provide implications to understand the behavior of zooplankton and nekton below the euphotic zone in the Southern Ocean.